Cooperation, cohesion and institutional volubility in the organizational systems of Chilean small traditional fisheries - Ascui Gac, Sebastián; Villegas Oliva, Claudio (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
In recent years, several investigations have contributed in understanding how institutions, formal and informal rules involving common pool resources, influence the outcomes and incentives of the agents’ roles inside institutional arrangements. The purpose of this article is to 1) give a formal ethnographically description of an institutional system nested in Chilean small scale fisheries. The analysis focuses on the strategies of multiple agents involved in the administration of a Benthic Resources Management Area (AMERB), awarded by a fishermen’s union in Caleta Coquimbo and 2) diluting how the incentives of these systems prescribe problems related to the volubility of organizations that pursue ecological sustainability for these traditional fisheries. Our research results show, in addition, the possibility of synergy between eminently qualitative methodologies such as ethnography and the making of explanatory mathematical models such as those used in Game Theory.